Disparate social structures are underpinned by distinct social rules across a primate radiation - Jacob A. Feder; Susan C. Alberts; Elizabeth A. Archie; Małgorzata E. Arlet; Alice Baniel; Jacinta C. Beehner; Thore J. Bergman; Alecia J. Carter; Marie J. E. Charpentier; Kenneth L. Chiou; Catherine Crockford; Guy Cowlishaw; et al. (Proceedings of the National Academy of Sciences, 2026)
Over six decades of research on wild baboons and their close relatives (collectively, the African papionins) have uncovered substantial variation in their behavior and social systems. While most papionins form discrete social groups (single-level societies), a few others form small social units that are nested within larger supergroups (multi-level societies). These two systems are generally thought to be qualitatively distinct, but data from wild populations increasingly suggest that there may be areas of overlap. To quantify this potential gradient in social structure, a more systematic, comparative analysis is needed. Here, we constructed a database of behavioral and demographic records spanning 135 group-years, 28 social groups, 13 long-term field studies, and 11 species to quantify variation in grooming network structure and identify the individual and dyadic properties (e.g., kinship and social status effects) that underlie this variation. Consistent with accumulating field observations, the single-level species could be divided into two categories: cohesive and cliquish . Cohesive single-level networks were dense, kin-biased, and moderately rank-structured, while cliquish single-level networks were more differentiated, slightly more kin-biased, and strongly rank-structured. As expected, multi-level networks were very modular and shaped by females’ ties to specific dominant males but varied in their kin biases. Taken together, these data suggest that in the African papionins i) kin and rank biases are widespread but vary in their strength; ii) male-centered subgroups are exclusive to multi-level systems; and iii) increases in network modularity can emerge in response to heightened nepotism and male-centered clustering.